Percepção do familiar cuidador sobre a assistência recebida no Centro de Atenção Psicossocial Infantojuvenil - Silveira, Edith Ana Ripardo da (2014)
The study aimed to analyze the attention paid to the family of children and adolescents assisted in Psychosocial Care Center Children and Juvenil- CAPSi. Descriptive and exploratory research with a qualitative approach. Data were collected in two existing CAPSi in Fortaleza (CE). Participated in the study sixteen family caregivers of children and adolescents who met the inclusion criteria. The total number of participants was defined according to data saturation. The production of empirical material was performed through an interview, using a script consists of two parts: the first social demographic aspects of the family caregiver and child and adolescent; the second, composed of a script containing questions that met the research objectives. For discussions used the thematic analysis, based on Bardin Content Analysis. The study was approved by the Ethics Committee of the Federal University of Ceará, under Opinion 321,012. Given the findings, we noted that CAPSi do not include all the criteria set by the Psychiatric Reform, as the population to be served, the physical structure and the technical and occupational team, while attempting to accommodate the demands of specific population. As for sociodemographic data, mothers were the primary caregivers of children and adolescents in the study, mostly with the following characteristics: married; are in the productive age group; the home; of low education; with low income, supplemented by social benefits (scholarships and grants). The children of the study caregivers deal in their daily lives, with some conditions that may be considered unfavorable mental health, including highlighted: some do not attend school; dependence to perform ADLs; socioeconomic and poor housing conditions; often, the overhead of these children and adolescents in therapeutic activities and the use of psychotropic medication. Of the guiding questions review process revealed three categories and 11 subcategories. The first category comprises the operations of teams in CAPSi: highlight the groups as the main activity of support; only one family mentioned individual care and care at home. The second category is associated with satisfaction and dissatisfaction of family: the absolute number it is satisfied with the service received. The third category brings the family expectations about the desired assistance. We show that even if feeling satisfied with the care they mention that wish there were more group sessions, more medical care, improvement in care, diversification of activities, transportation vouchers and benefits. Considered to have reached the proposed objectives and we hope that this study offers subsidies to reflect on the practice in the new mental health services, seeking to approach them from providing for the psychiatric reform that meets the principles of SUS. In addition, we hope to be contributing to the critical reflection of the nurse practice in mental health care.